2016
DOI: 10.1063/1.4948955
|View full text |Cite
|
Sign up to set email alerts
|

Going beyond 20 μm-sized channels for studying red blood cell phase separation in microfluidic bifurcations

Abstract: Despite the development of microfluidics, experimental challenges are considerable for achieving a quantitative study of phase separation, i.e., the non-proportional distribution of Red Blood Cells (RBCs) and suspending fluid, in microfluidic bifurcations with channels smaller than 20 lm. Yet, a basic understanding of phase separation in such small vessels is needed for understanding the coupling between microvascular network architecture and dynamics at larger scale. Here, we present the experimental methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
57
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(69 citation statements)
references
References 51 publications
12
57
0
Order By: Relevance
“…2B. We observed a drastic reduction of the hematocrit when the suspension passed from the reservoir into the microdevice which is in line with other observations11. This could be explained by the Fåhræus effect4243 and by residual particle sedimentation in the reservoir (despite the use of Optiprep).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…2B. We observed a drastic reduction of the hematocrit when the suspension passed from the reservoir into the microdevice which is in line with other observations11. This could be explained by the Fåhræus effect4243 and by residual particle sedimentation in the reservoir (despite the use of Optiprep).…”
Section: Discussionsupporting
confidence: 90%
“…This results in a reduction of the flow rate difference between the two daughter branches. The basic mechanisms have been extensively investigated in single bifurcations6891011. In networks of bifurcating (diverging and converging) vessels, RBC dynamics becomes more complex and often counter-intuitive5121314151617.…”
mentioning
confidence: 99%
“…Indeed, a recent in vitro study of phase separation in microchannels beyond 20 μm concluded that “These data clearly show that the ‘ad hoc’ law proposed by Gould and Linninger is inappropriate for parametrizing the phase separation effect. By contrast, they are consistent with the empirical description of Pries et al.”…”
Section: Introductionsupporting
confidence: 88%
“…22 Indeed, a recent in vitro study of phase separation in microchannels beyond 20 μm concluded that "These data clearly show that the 'ad hoc' law proposed by Gould and Linninger is inappropriate for parametrizing the phase separation effect. By contrast, they are consistent with the empirical description of Pries et al" 23 Of note, Gould and Linninger based part of their analysis on a network representation that they derived from a photomontage of a mesentery network, originating for a database of 7 networks. 5 The PS model has previously been shown to provide plausible hematocrit predictions on these networks.…”
Section: Networksupporting
confidence: 79%
“…The model was used to calculate the flow and hematocrit in each vessel and the pressure at each intersection of vessels. For the human dataset, the parameters for the empirical descriptions of the Fåhraeus, Fåhraeus -Lindqvist and phase separation effects were re-scaled in order to account for the difference in characteristic size between human and rat RBCs, as proposed by Lorthois et al 23 and Roman et al 60 . This simulation approach has no free parameters.…”
Section: Blood Flow Simulationsmentioning
confidence: 99%